1999
DOI: 10.1116/1.590733
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam epitaxial growth of normal and inverted two-dimensional electron gases in AlGaN/GaN based heterostructures

Abstract: Two-dimensional electron gases in AlGaN/GaN heterostructures grown by plasma induced molecular beam epitaxy have been formed by polarization induced interface charge effects. Growth of the “normal” structure (AlGaN on GaN) has formed a two-dimensional electron gas confined in the GaN when grown on sapphire with an AlN nucleation layer, SiC (Si face), or on GaN nucleated by organometallic vapor phase epitaxy on sapphire. Hall mobilities in GaN for normal interfaces are as high as 1238 cm2/V s at 300 K and 3182 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 11 publications
1
17
0
1
Order By: Relevance
“…The deposition was started growing a 10 nm AlN nucleation layer followed by a 2 mm thick GaN buffer layer. With this thin AlN nucleation layer the polarity of the thick GaN layer was changed from normally N-face to Ga-face [12]. Next a 30 nm thick Al x Ga 1--x N barrier layer with an aluminum content of 30% was grown to form a two-dimensional electron gas (2DEG) at the GaN/AlGaN interface (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The deposition was started growing a 10 nm AlN nucleation layer followed by a 2 mm thick GaN buffer layer. With this thin AlN nucleation layer the polarity of the thick GaN layer was changed from normally N-face to Ga-face [12]. Next a 30 nm thick Al x Ga 1--x N barrier layer with an aluminum content of 30% was grown to form a two-dimensional electron gas (2DEG) at the GaN/AlGaN interface (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A 7 nm thick AlN buffer layer was then grown at 800°C to control the GaN polarity. 2,3 The heterostructures are composed of a 25 nm AlGaN barrier layer of nominal 30% Al concentration grown on a GaN buffer layer of thickness 1 µm and then capped with 2 nm of GaN (see Fig. 1).…”
Section: Experimental Approachmentioning
confidence: 99%
“…It was recently reported that high temperature annealing of AlN nucleation buffer on sapphire resulted in Ga-polarity material by MBE. 13 However, since sapphire is not a polar substrate, this way of obtaining a Ga-polar film is achieved by weeding out the undesired N-polar nucleation layer. 14 This requires optimization of several steps including buffer deposition and anneal.…”
Section: Resultsmentioning
confidence: 99%